Al-Sirri v. Secretary of State for the Home Department; DD (Afghanistan) v. Secretary of State for the Home Department. (2015) - Unknown
Abstract : 616 Aliens — Refugees — Asylum applicants — Determination of refugee status — Exclusion from protection due to commission of international crimes — Convention relating to the Status of Refugees, 1951 — Article 1F(c) — Whether acts of terrorism requiring "international dimension" to constitute "acts contrary to the purposes and principles of the United Nations" — Whether armed attacks against an armed, United Nations-mandated force in principle falling within Article 1F(c) — Standard of proof — Whether "serious reasons for considering" equivalent to a criminal standard of proof — Whether membership of organization that has committed international crimes sufficient International organizations — United Nations — Principles and purposes — United Nations Charter, Article 1 — Security Council — United Nations forces — Conflict in Afghanistan — International Security Assistance Force ("ISAF") — Authorization by Security Council — Whether attacks on ISAF acts contrary to the purposes of the United Nations — Refugee Convention, Article 1F(c) Relationship of international law and municipal law — Treaties — Interpretation — Charter of the United Nations, Articles 1 and 2 — Purposes and principles of the United Nations — Convention relating to the Status of Refugees, 1951 — Article 1F(c) — Terrorism Act 2000, Section 1 — Whether activities defined as terrorism under domestic law contrary to purposes and principles of United Nations — Whether activities having to constitute threat to international peace and security or to peaceful relations between nations to fall within Article 1F(c) of Refugee Convention — Whether armed attacks against armed, United Nations-mandated force falling within Article 1F(c) of Refugee Convention Terrorism — Definition — Position under domestic law — Position under international law — Whether terrorist activities contrary to principles and purposes of United Nations — Whether international dimension or repercussions for international peace and security necessary — Whether activities falling within Article 1F(c) of Refugee Convention — The law of England